2014
DOI: 10.1017/s1368980014000664
|View full text |Cite
|
Sign up to set email alerts
|

Association between home availability and vegetable consumption in youth: a review

Abstract: Objective: To systematically review literature examining the association between vegetable home availability and vegetable intake in youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 34 publications
(252 reference statements)
2
26
0
Order By: Relevance
“…Increased availability of fruit and vegetables at home predicted higher intake of vegetables too. Such findings corroborate previous literature (Cook et al., 2015, Pearson et al., 2009), but extend it by also considering the role of accessibility and availability of ED snack foods as predictors of healthy food intake. Unsurprisingly, home availability of ED snack foods was a strong predictor of ED snack food intake, further reinforcing the importance of the physical environment in determining adolescents' eating behaviours.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Increased availability of fruit and vegetables at home predicted higher intake of vegetables too. Such findings corroborate previous literature (Cook et al., 2015, Pearson et al., 2009), but extend it by also considering the role of accessibility and availability of ED snack foods as predictors of healthy food intake. Unsurprisingly, home availability of ED snack foods was a strong predictor of ED snack food intake, further reinforcing the importance of the physical environment in determining adolescents' eating behaviours.…”
Section: Discussionsupporting
confidence: 93%
“…Eating meals as a family and parental role modelling have both been associated with healthier adolescent eating behaviours (Fink et al., 2014, Gillman et al., 2000). Availability and accessibility of foods are powerful predictors of consumption, with greater availability and accessibility of fruits and vegetables being related to greater intake in children and adolescents (Cook et al., 2015, Loth et al., 2016, Pearson et al., 2009). Furthermore, not making unhealthy foods available or accessible, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…As highlighted, the identified FFQ varied considerably on comprehensiveness (number of items) and detail (use of broad terms like 'fruit' or 'vegetables' v. specific items). While cut-offs such as that used by Cook et al (151) may be applied, any judgement on comprehensiveness must be balanced against the purpose of the assessment; for example, is the aim is to examine dietary patterns overall, rather than focus specifically on health and disease associations with individual fruits and vegetables, and is there additional benefit to be gained from providing an exhaustive list? However, where broad terms are included, this needs to be supplemented with adequate explanation or an inventory of items intended to fall under these terms, to avoid the possibility of participant misunderstanding and consequently variation across countries and regions.…”
Section: Public Health Nutritionmentioning
confidence: 99%
“…Empirical studies have shown that availability and access to food are essential, but they are not the only factors that ensure household food and nutrition security (Brown & Funk, 2015; Cook, Reilly, Derosa, Rohrbach, & Spruijt‐metz, 2014; Ozor, Umunnakwe, & Acheampong, 2014). Nutritional knowledge and attitude have been shown to influence dietary practices and consequently the quantity and quality of nutrients derived from a given food item (Hoogenboom, Morris, Morris, & Schaefer, 2009; Sichert‐hellert et al., 2011).…”
Section: Introductionmentioning
confidence: 99%